CT Scan Features of Presumptive Haemorrhagic Stroke in a Dog with Cushing’s Disease - A. Liotta; R. Cavrenne; D. Peeters; J. Manens; G. Bolen (Case Reports in Veterinary Medicine)
A 9-year-old, intact male, Brie’s shepherd dog, with a 10-day history of depression and tachypnoea developed signs of central neurological dysfunction. 16 Multislice Computed Tomography (CT) pre- and postcontrast studies of the brain revealed a single intra-axial homogeneous well-circumscribed hyperattenuating (+/− 62 HU) and noncontrast-enhancing area, 5 mm in diameter, in the caudal part of the mesencephalon. This finding was highly suggestive of a haemorrhagic event. A pituitary-dependent hyperadrenocorticism (PDH) was identified and is considered likely to be the underlying cause. A repeat CT scan examination, 2 months later, showed almost complete resolution of the brain lesion. The present case describes a solitary 5 mm diameter lesion: the result of intracranial haemorrhage in a dog with presumed PDH.